Theorising Transformative Learning : The Power of Autoethnographic Narratives in Education. - Pandey, Kashi Raj (BRILL, 2021)
Educational reality is weaved within stories, poems, and dialogues, as the author demonstrates his becoming of a transformative educator. Transformative learning is important for teachers to think about their practices, change their thinking, and share the stories of their experience for learners' empowerment. This is an autoethnographic account of the author's experience as a transformative and transforming educator that unfolds the ways he has used ethical dilemma story pedagogy to explore interpretative and creative spaces for transformative learning, both personally and with a group of trainee teachers who take the responsibility to facilitate students' learning into a purposeful path. The ethical dilemma story pedagogy provides relatable scenarios to challenge and unsettle learners' thought processes leading to acknowledgment of multiple viewpoints. Theorising Transformative Learning serves to help educators utilise the sociocultural contexts connected to students' lives and experiences.
Description based upon print version of record.
Keywords: Pandey, Kashi Raj.; Transformative learning.; Critical pedagogy.; Ethnology -- Authorship.; Ethnology -- Research.; Ethnology -- Methodology.; Apprentissage transformateur.; Pédagogie critique.; Ethnologie -- Recherche.; Ethnologie -- Méthodologie.; Critical pedagogy; Ethnology -- Authorship; Ethnology -- Methodology; Ethnology -- Research; Transformative learning; Electronic book.